Improvement of grain alignment in Bi2Sr2Co1.8Oy thermoelectric through the electrically assisted laser floating zone. (October 2020) - Ferreira, N.M.; Madre, M.A.; Torres, M.A.; Davarpanah, A.; Amaral, V.; Costa, F.M.; Sotelo, A.
Graphical Abstract: Improvement the thermoelectric performance of Bi2 Sr2 Co1.8 Oy due to the annealing of the samples grown by electrically assisted laser floating zone. Highlights: Multiphasic textured Bi2Sr2Co1.8Oy thermoelectric materials here grown by EALFZ; The external current allows to control the number and amount of secondary phases; Annealed samples present low secondary phases originate higher TE performances; Highest ZT values (0.09) have been achieved at 650 ºC for 300 mA grown samples; The samples here prepared can be used directly for integration in TE modules. Abstract: Thermoelectric performances of cobaltite ceramics were improved by increasing grain sizes and alignment through the Electrically Assisted Laser Floating Zone method. Bi2 Sr2 Co1.8 Oy ceramics were directionally grown at 30 mm/h, applying external DC (0-500 mA) during the growth process . Microstructure and thermoelectric properties are significantly influenced by the external current direction and intensity. Negative currents/pole on the seed rod prevent the formation of thermoelectric phase, while positive pole on the seed rod, decreases the amount of secondary phases and increase grain orientation when compared to samples grown without current. Annealing procedure decreases secondary phases content, without modifying grain alignment. The best thermoelectric performances were obtained for samples grown with +300 mA, reaching the highest ZT values of 0.09 at 650 °C. Moreover, it should be highlighted that these processed samples can be directly applied in thermoelectric modules, avoiding the long and expensive steps necessary when other preparation processes are used .